2019
DOI: 10.1042/bsr20181794
|View full text |Cite
|
Sign up to set email alerts
|

Knocking down of LINC01220 inhibits proliferation and induces apoptosis of endometrial carcinoma through silencing MAPK11

Abstract: Background: Endometrial carcinoma (EC) still threatens the health of women. Thus, to explore how long intergenic non-protein coding RNA 01220 regulates the development of EC. Methods: Whole genome expression profile data of EC and paracancerous tissues in TCGA database were downloaded. LINC01220 expression in EC and paracancerous tissues of patients in our hospital were detected by qRT-PCR. Furthermore, the relationship between LINC01220 expression and clinicopathological features of EC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
(28 reference statements)
1
15
1
Order By: Relevance
“…11 LINC01220 expression is dramatically up-regulated in EC tissues and its high expression is strongly associated with tumor stage. 30 Consistent with the above two findings, we revealed that the expression of LINC01106 was obviously elevated in EC tissues and cells, and high expression of LINC01106 presented a notable connection with the tumor stage. In addition, we also demonstrated that LINC01106 was correlated with tumor metastasis.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…11 LINC01220 expression is dramatically up-regulated in EC tissues and its high expression is strongly associated with tumor stage. 30 Consistent with the above two findings, we revealed that the expression of LINC01106 was obviously elevated in EC tissues and cells, and high expression of LINC01106 presented a notable connection with the tumor stage. In addition, we also demonstrated that LINC01106 was correlated with tumor metastasis.…”
Section: Discussionsupporting
confidence: 88%
“…2,3 Many lncRNAs are taken part in the occurrence of EC. 11,30 LINC01410 is highly expressed both in EC tissues and cells and the up-regulation of LINC01410 is closely related to tumor stage. 11 LINC01220 expression is dramatically up-regulated in EC tissues and its high expression is strongly associated with tumor stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In endometrial cancer, p38β has been shown to mediate the proliferation of tumor cells by inhibiting apoptosis. In this case, the anti-apoptotic ability of p38β seems to be controlled by the long non-coding RNA 1220, that controls p38β expression [ 90 ]. Interestingly, in lung cancer it has been recently reported that p38α, but not the rest of p38MAPK members, could be a potential biomarker of chemotherapy response [ 68 ].…”
Section: P38β and Cancermentioning
confidence: 99%